Technological Change and Small Enterprises in Greece: Investments, Digital Technologies and Digital Policies - Angelakis, Antonios (HAPSc Policy Briefs Series, 2022)
Disruptive technological progress is rapidly changing critical dimensions of social and economic activity. Within the domain of small enterprises particularly, technological change constitutes a cross-cutting driving force of transformation across the spectrum of the value chains (e.g. manufacturing, distribution, marketing, logistics). However, the digital transition is characterized by strong asymmetric trends of differentiation depending on a wide set of parameters. Under this prism, emerging paradigms of digital policies is a key policy mechanism for accelerating and symmetrically diffusing digital adaptation.